Troubleshoot your PC with Jean Andrews - Andrews, Jean (Thomson Course Technology, 2004)
This book is written for the PC technician and troubleshooter who may be facing a PC problem, but has no idea what is causing it. It is also useful for the PC user who might know which of their PC's subsystems is in trouble, but are just not sure how to remedy the situation. Either way, this book points the reader to a series of step-by-step instructions and flowcharts to follow. Including information on Windows XP, Windows 2000, and Linux, this is an essential tool for anyone who needs to find PC information quickly and efficiently. The reader starts off by consulting the Troubleshooting Roadmap, which points them to the right section of the book that will give them the answer. Additionally, checklists and a quick reference of the top-ten PC problems are included so the remedies to common issues are easy to find. Readers can also search by system or symptom to solve computer problems fast